Piezo- and Magnetoelectric Polymers as Biomaterials for Novel Tissue Engineering Strategies. (20th February 2018) - Ribeiro, C.; Correia, D.M.; Ribeiro, S.; Fernandes, M. M.; Lanceros-Mendez, S.
ABSTRACT: Tissue engineering and regenerative medicine are increasingly taking advantage of active materials, allowing to provide specific clues to the cells. In particular, the use of electroactive polymers that deliver an electrical signal to the cells upon mechanical solicitation, open new scientific and technological opportunities, as they in fact mimic signals and effects that occur in living tissues, allowing the development of suitable microenvironments for tissue regeneration. Thus, a novel overall strategy for bone and muscle tissue engineering was developed based on the fact that these cells type are subjected to mechano-electrical stimuli in their in vivo microenvironment and that piezo- and magnetoelectric polymers, used as scaffolds, are suitable for delivering those cues. The processing and functional characterizations of piezoelectric and magnetoelectric polymers based on poly(vinylindene fluoride) and poly-L-lactic acid in a variety of shapes, from microspheres to electrospun mats and three dimensional scaffolds, are shown as well as their performance in the development of novel bone and muscle tissue engineering.